Serum vascular endothelial growth factor levels in bitches with canine transmissible venereal tumors treated with vincristine sulphate - Esra Kocabaş; Özkan Duru; Hasan Ceyhun Macun (Eurasian Journal of Veterinary Sciences)
Aim: The present study aimed to determine the serum concentrations of vascular endothelial growth factor (VEGF), which is an important factor in tumor angiogenesis, in dogs with transmissible venereal tumor (TVT) and to evaluate the levels of this factor in treatment with vincristine sulphate. On the other hand, the relationship between VEGF level and the number of vincristine sulphate applications was investigated. Materials and Methods: Study material is consisted of twelve Kangal Shepherds and its crossbreds without ovariohysterectomy (OHE) diagnosed with TVT (study group)and 12 healthy Kangal Shepherds and its crossbreds without OHE (control group). Blood was drawn from 12 dogs included in the study group before each treatment and one week after the end of the treatment. Blood was drawn once from the dogs in the control group. Results: All cases in the study group were treated with 3-8 (4,33±1,43) vincristine sulphate administrations. Three of the patients recovered with 3, 6 of the dogs with 4, 1 with 5, 1 with 6 administrations and 1 with 8 weeks of administrations. In the correlation analysis that performed between the pre-treatment serum VEGF level and the number of vincristine sulphate administration, a statistically in significant positive correlation was found (r = 0,051). When serum VEGF values of dogs in the study group were compared with the pre-treatment serum VEGF values of dogs in the control group, no statistical difference was found (p = 0,160). Conclusion: As a result, although serum VEGF values of dogs with TVT were higher than healthy dogs, it was determined that there was no statistical difference. No correlation was found between pre-treatment serum VEGF value and number of applications.